Vessel transportation scheduling optimization based on channel–berth coordination. (15th January 2016) - Zhang, Xinyu; Lin, Jun; Guo, Zijian; Liu, Tieshu
Abstract: Channels and berths are important resources for vessels in port operation. This study aims to improve the efficiency of vessel transportation scheduling by coordinating channels and berths. Therefore, in consideration of scheduling order, travel direction and distance of the berth, a mathematical model with minimum total waiting time as the objective function is established. Furthermore, it applies a simulated annealing and multiple population genetic algorithm (SAMPGA) to solve the proposed model for vessel transportation scheduling in port. This study simulates numerical examples for 10 and 20 vessels. Calculations indicate waiting and total scheduled times of 485 min and 342 min, respectively, for 10 vessels and 1731 min and 456 min, respectively, for 20 vessels. Compared with the simple genetic algorithm (SGA) and the "first come, first served" (FCFS) method, the total waiting time, scheduled time, and maximum waiting time are decreased significantly through SAMPGA. The results show that the proposed model and algorithm can ensure safety and improve the efficiency of vessel transportation scheduling simultaneously. Highlights: Establish a vessel scheduling mathematical model coordinating channel and berth. Simulated annealing and multiple population genetic algorithm is used to computing. Simulated numerical examples to validate the model and algorithm. Optimal schedule solution ensures port safety for vessels. Optimal schedule solution increases port efficiency in the same condition.